PENGARUH PERPUTARAN MODAL KERJA TERHADAP KINERJA STUDI KASUS PADA PT. CIPUTRA SURYA TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005 – 2013 - Andika Nugraha; Darsawati, Eris (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
The purpose of this research is to find out the influence of working capital turnover to the performance PT. Ciputra Surya Tbk which were listed in Indonesian Stock Exchange during 2005-2013. The variables used in this research are working capital turnover and performance. The samples taken of this research were obtained from financial statements of PT. Ciputra Surya Tbk with total 36 of quarterly financial statements reports during 2005-2013. The Sampling method used was purposive sampling, that is sampling technique with particular consideration based on interests or research purposes. This research uses the classical assumption test, simple regression test, Pearson coefficient test, t test, and test R ² (coefficient of determination). Of some test results that have been conducted by the author in this research, especially of the t test results showed that the working capital turnover significantly affect the performance of the PT. Ciputra Surya Tbk.